Gold-catalyzed cascade C–H/C–H cross-coupling/cyclization/alkynylation: an efficient access to 3-alkynylpyrroles1. Issue 21 (7th June 2015) - Zhang, Shuai; Ma, Yuanhong; Lan, Jingbo; Song, Feijie; You, Jingsong
<x xml:space="preserve">Abstract</x> An efficient approach to 3-alkynylpyrroles has been developed through the gold-catalyzed cascade oxidative C–H/C–H cross-coupling, cyclization and in situ oxidative alkynylation.